Performance of Growth and Remediation Potency of Jacaranda mimosifolia in Cadmium and Lead Contaminated Soil - El-Sayed El-Mahrouk; Hayam M.A. Ebrahim; Mohamed K. Gaber; Mahmoud A. Aly; Assem A.M. El-Naggar; Péter Honfi; Andrea Tilly-Mándy; Eman Abdelhakim Eisa (BioResources)
In a 16-month study addressing global agricultural soil heavy metal contamination, researchers explored plant-centered solutions using Jacaranda plants. The impact of different combinations of cadmium nitrate (40, 80, and 120 mg) and lead nitrate (400, 800, and 1200 mg/kg soil) were evaluated relative to Jacaranda’s remediation capabilities. Employing a randomized complete block design with 8 applications across 3 repetitions, the study assessed growth traits and chemical characteristics. Untreated plants showed higher growth values, contrasting with reduced values in plants exposed to elevated cadmium (Cd) and lead (Pb) levels. For instance, the treatment with 120 mg Cd/kg soil + 1200 mg Pb/kg soil led to a 28% reduction in plant height, 13% in main stem diameter, 41% in branch number, and 35% in leaf area compared to the control. Despite these challenges, Jacaranda plants demonstrated resilience with a 100% survival rate. Plant organs showed increased Cd and Pb contents, with fallen leaves having lower metal content, mitigating pollution hazards. Post-planting, soil characteristics shifted, indicating Jacaranda's potential for Cd phytoextraction (BCF < 1 and, TF > 1) and Pb phytostabilization (BCF and TF < 1). The study establishes Jacaranda as a promising candidate for phytoremediation due to its resilience to elevated metal levels.